A cognitive tool to support mathematical communication in fraction word problem solving - Ahmad, A.; Salim, S.S.; Zainuddin, R. (2008)
Abstract: Word problem solving is one of the most challenging tasks in mathematics for most students. It requires the solver to translate the problem into the language of mathematics, where we use symbols for mathematical operations and for numbers whether known or unknown. From a study conducted on Malaysian school students, it was found that majority of them did not write their solution to the word problem using correct mathematical language. Intrapersonal and interpersonal communications are important in mathematics learning especially in word problem solving. It is therefore the main aim of this paper is to present a model that promotes the use of mathematical language. The model is used as a basis in designing a computer-based learning environment for word problem solving. The cognitive tool named MINDA which incorporates several important necessary steps and activities was developed to facilitate learning. From the experimental analysis conducted on using MINDA, it was found that the mathematical communication and their word problem solving achievement of students have improved.